Pengelolaan Manajemen Risiko Kehilangan Pada Indomaret Raya Jonggol Cileungsi KM 10 - Kiki Kurniawan; Nuryanto Nuryanto (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The research entitled Management of Loss Risk Management at Indomaret Raya Jonggol Cileungsi Km 10. This study aims to determine the management of risk management for the prevention of loss of goods, and aims to determine efforts to resolve lost goods at Indomaret Raya Jonggol Cileungsi KM 10. The results show that Indomaret has implemented several risk management practices to reduce losses such as the use of CCTV and strict stock counting procedures. However, there are still some weaknesses in managing the risk of loss such as security when the shop is closed at night, there is no guard such as security in the shop-house area which is at risk of theft. Therefore, security is needed in the shop area to reduce the risk of loss. Keywords: Management, Risk of loss, management.